Monocyte to High-Density Lipoprotein Ratio Is Associated With Early Neurological Deterioration in Acute Isolated Pontine Infarction - Bi, Xinwei; Liu, Xiaoqian; Cheng, Jiaqi (Frontiers in Neurology, 2021)
Objectives: Monocyte to high-density lipoprotein ratio（MHR）has been considered to be a novel inflammatory marker of atherosclerotic cardiovascular disease.However, its role in the acute phase of acute isolated pontine infarctions remains elusive. To explore whether an association existed between elevated MHR levels and early neurologic deterioration (END) in patients with isolated pontine infarction. Methods: Data from 212 patients with acute isolated pontine infarction were retrospectively analyzed. END was defined as an elevation in the NIHSS score by ≥1 point in motor power, or ≥2 point in the tatal score within 7 days after symptom onset. Results: The mean MHR level was 0.44±0.22. A total of 58(27.36%) patients were diagnosed with END. 38 patients(65.52%) of the END cases occured within the first 48 hours after admission. The odds ratio for END increased with increasing quartile levels of MHR with the lowest quartile used as the reference value. Compared to the first quartile of MHR, the third quartile and the fourth quartile were associated with 4.847-fold and 5.824-fold increase in the odds of END. Conclusions: Eleveted MHR may be valuable as a predictor of prognosis in patients with isolated pontine infarction. Patients with acute isolated pontine infarction with elevated MHR levels are at an increased risk for END.